THE JIZZAKH REGIONAL MUSICAL DRAMA THEATRE: HISTORICAL DEVELOPMENT, ARTISTIC CONTRIBUTIONS, AND ITS PLACE IN UZBEK THEATRE STUDIES - Tursunoy Fayzullayeva (International Journal of Literature and Language Studies, 2026)
This article examines the scholarly study of Uzbek theatres, including dissertations and academic publications produced by researchers, as well as the increasing attention devoted to theatrical art. Particular emphasis is placed on the historical development of the Jizzakh Regional Musical Drama Theatre, its early productions, and the creative activities of its actors and directors. The article also explores the formation and evolution of the theatre, highlighting significant stages in its artistic development and contribution to the cultural life of the region.